Phosphate addition intensifies the increase in N2O emission under nitrogen deposition in wet meadows of the Qinghai-Tibet Plateau - Wu, Jiangqi; Wang, Haiyan; Li, Guang (Frontiers in Microbiology, 2024)
Alpine wet meadows are known as N2O sinks due to nitrogen (N) limitation. However, phosphate addition and N deposition can modulate this limitation, and little is known about their combinative effects on N2O emission from the Qinghai-Tibet Plateau in wet meadows. This study used natural wet meadow as the control treatment (CK) and conducted experiments with N (CON2H4 addition, N15), P (NaH2PO4 addition, P15), and their combinations (CON2H4 and NaH2PO4 addition, N15P15) to investigate how N and P supplementation affected soil N2O emissions in wet meadow of QTP. Contrary to previous studies on grasslands, the effect of phosphate addition treatment on soil N2O flux was not detectable during the growing seasons of 2019 and 2020. Over a span of two years, the N addition treatment significantly increased the N2O flux by 3.45 μg⋅m–2⋅h–1 due to increased soil N availability. Noticeably, phosphate addition intensified the effect of N deposition treatment on soil N2O flux with high significance in the early growth season of 2020. This augmentation can be attributed to the alleviation of limiting factors imposed by plants and microorganisms on soil N and P, fostering the mineralization and decomposition of litter and soil nutrients by microorganisms. Consequently, the results showed that total nitrogen and nitrate nitrogen were the main controls on soil N2O emission under N and P addition. In addition, redundancy analysis showed that the relative abundance of NirK genes in soil microorganisms (Bradyrhizobium, Devosia, Ochrobactrum, Alcaligenes, Rhizobium) is the main factor affecting N2O flux and available nitrogen. We project that if nutrient input continues to increase, the main limiting factor of soil will change from N restriction to P restriction due to the unique microbial nitrogen conversion process in the alpine meadow, significantly increasing N2O emissions. Consequently, the heightened contribution of alpine wet meadows to global warming and ozone depletion hinges on the dynamics of nutrient input regimes, spotlighting the urgent need for informed environmental management strategies.